Evidence‐Based Management Competency Model for Managers in Hospital Settings. (27th September 2020) - Daouk‐Öyry, Lina; Sahakian, Tina; van de Vijver, Fons
Abstract: Evidence‐based management (EBMgt), which refers to using the best‐quality evidence from different sources in decision‐making, is becoming an imperative for managers in both profit and non‐profit sectors. Yet, the competencies underlying EBMgt have not yet received much attention. Therefore, the aim of this study is to identify the foundational and functional competencies of evidence‐driven managers working in hospital settings and develop an empirically based competency model for evidence‐driven managers. We collected qualitative data using semi‐structured interviews and the critical incident technique from 36 executive managers from 11 hospitals in Lebanon about the competencies of managers who use EBMgt when approaching problems and making decisions. Using inductive coding, we identified 13 competencies that we grouped into four dimensions: technical, cognitive, interpersonal and intrapersonal. We further classified the specific competencies underlying each of the dimensions into foundational and functional, and highlighted those that are critical for the practice of EBMgt in hospital settings, including open mindedness, research knowledge and skills, ethicality in research, resourcefulness and relationship management.